2018
DOI: 10.1002/jcp.27400
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA XIST is associated with poor prognosis in human cancers

Abstract: Growing evidence from recent studies has shown that the X-inactive specific transcript (XIST), a well-known long noncoding RNA involved in early embryonic development, is aberrantly regulated in various human cancers. However, the prognostic value of XIST in cancers remains uncharacterized. In this study, we searched PubMed, Web of Science, and Embase to collect all relevant studies, and a meta-analysis was performed to explore the association of XIST expression with overall survival (OS) and clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…XIST appears to be both tumor-promoting and tumorsuppressive, depending on cancer type and context [118]. Surprisingly, two meta-analyses of XIST in cancer identified no association between XIST and sex/gender, but did find that high levels were associated with poor overall survival [119,120]. Although XIST is not normally expressed in XY cells, these studies suggest that aberrant regulation of this lncRNA can occur in both male and female tumors.…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 82%
“…XIST appears to be both tumor-promoting and tumorsuppressive, depending on cancer type and context [118]. Surprisingly, two meta-analyses of XIST in cancer identified no association between XIST and sex/gender, but did find that high levels were associated with poor overall survival [119,120]. Although XIST is not normally expressed in XY cells, these studies suggest that aberrant regulation of this lncRNA can occur in both male and female tumors.…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 82%
“…It has been well documented that lncRNA XIST acts as an oncogenic factor, driving the formation and growth of cancer cells, promoting the epithelial–mesenchymal transition, and indicating poor prognosis in human cancers 1921. However, little is known about its role in the polarization of tumor-associated macrophages, an important cellular program during tumor progression 22.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence from recent studies has shown that lncRNA Xist facilitates tumor development, including pituitary neuroendocrine tumor, neuroblastoma, thyroid cancer, colon cancer, renal cell carcinoma, and prostate cancer ( Chaligne and Heard, 2014 ; Yang Z. et al, 2018 ; Liu et al, 2019c ). In the pituitary neuroendocrine tumor cells ( Zhou et al, 2019b ), lncRNA Xist, which functions as a ceRNA to sequester miR-424-5p to elevate the expression of the its target bFGF, and exhibits high expression in invasive pituitary neuroendocrine tumor tissues as compared to non-invasive tumor tissues, promotes cancer progression in invasive pituitary neuroendocrine tumor via activating the miR-424-5p/bFGF signaling pathway.…”
Section: The Role Of Lncrna Xist In Cancermentioning
confidence: 99%